Elections and civil violence in new multiparty regimes: Evidence from Africa. (September 2015) - Goldsmith, Arthur A
The introduction of multiparty competition around the world following the Cold War raises the specter of rising civil violence during election periods in emerging democracies and hybrid regimes. Yet there are also plausible theoretical reasons to expect dropping civil violence around elections in these states or, alternatively, no significant change in the level of such conflict. This article tests these hypotheses in Africa with the aid of event data on the daily rate of civil violence incidents (1997–2013). It asks if civil violence in that region is more frequent, less frequent or constant during election cycles compared to other times. To guard against definitional and data selection problems encountered in some prior cross-national studies of elections and use of force, the research design emphasizes the relative risk of social conflict at the national level. The analysis suggests three distinct patterns in Africa. Given countrywide norms, election periods in most countries run the same relative risk of a day with violent events as do non-election periods. A subset of African countries exists, however, with more civil violence during elections when judged against the national reference line for conflict. There is a smaller group of countries where the risk of electoral civil violence is comparatively low. While caution should be exercised in interpreting the findings, the policy implication is that no general reason exists to preclude or defer elections in Africa as a way to minimize social conflict associated with political campaigns, although there may be specific reasons to do so in particular countries.